Die Gesetze der Angelsachsen : Herausgegeben im Auftrage der Savigny-Stiftung. edited and translated by Felix Lieberman. - Liebermann, F. (Felix), 1851-1925; Liebermann, F. (Felix), 1851-1925 (Cambridge library collection., 2015)
This edition of the laws promulgated by successive Anglo-Saxon rulers over a period of five centuries was published in three volumes between 1903 and 1916 by the German historian Felix Lieberman (1851-1925), and is still regarded as authoritative. This unique body of early medieval legal writing, unparalleled in other Germanic languages, provides valuable source material for scholars of Old English and of legal history, and Lieberman's thorough engagement with the manuscripts has never been surpassed. Volume 3 provides introductions to each set of laws presented in Volume 1, and detailed line-by-line explanatory notes that complement the dictionary and glossary of terms found in Volume 2. Frederick Attenborough's The Laws of the Early English Kings (1922), providing a modern English translation of early Anglo-Saxon laws, is also reissued in this series.